Chitosan Coupling Makes Microbial Biofilms Susceptible to Antibiotics - Zhang, Amin (Nature Publishing Group, 2013)
Microbial biofilms, prevalent in nature and inherently resistant to both antimicrobial agents and host defenses, can cause serious problems in the chemical, medical and pharmaceutical industries. Herein we demonstrated that conjugation of an aminoglycoside antibiotic (streptomycin) to chitosan could efficiently damage established biofilms and inhibit biofilm formation. This method was suitable to eradiate biofilms formed by Gram-positive organisms, and it appeared that antibiotic contents, molecular size and positive charges of the conjugate were the key to retain this anti-biofilm activity. Mechanistic insight demonstrated chitosan conjugation rendered streptomycin more accessible into biofilms, thereby available to interact with biofilm bacteria. Thus, this work represent an innovative strategy that antibiotic covalently linked to carbohydrate carriers can overcome antibiotic resistance of microbial biofilms, and might provide a comprehensive solution to combat biofilms in industrial and medical settings.